Optimization Activities Elderly Health Care Center in Coastal Village of Ulak Karang Selatan, Padang City - Yaslina, Yaslina; Yaswinda, Yaswinda; Yulsyofriend, Yulsyofriend; Elida, Elida (Universitas Negeri Padang, 2022)
The success of Indonesia's health development is inseparable from the active participation of the community. One of the community-based health efforts that has been developed is the the elderly health care center . The level of cadres' ability in managing the health care for the elderly greatly influences the effectiveness of the health care, it is necessary to hold cadre training to improve the capabilities of the elderly Posyandu cadres. The results of interviews with the Community Service Team stated that the elderly health care are already running but are felt to be less than optimal, due to the small number of health care cadres and the limited knowledge of cadres. Service methods used for cadre training are lectures, role play, demonstrations as well as mentoring as well as monitoring and evaluation. The material provided was 6 material with activities carried out on June 2019 - September 2019 for 5 days in RW 01 of Ulak Karang Selatan Village. After the training activities were carried out there was an increase in the average knowledge that is with an average of 86.3 and an increase in cadre skills with an average of 85.1 after the cadre training activities were carried out.